(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The present study was designed to investigate the antinociceptive, anti-inflammatory and hypoglycemic effects of petroleum ether, carbon tetrachloride, dichloromethane and ethyl acetate soluble partitionates of the methanolic extracts of Terminalia citrina leaves. The partitionates of the methanolic extract of the leaves of plant T. citrina at 200 mg/kg and 400 mg/kg were subjected for their antinociceptive activity using both acetic acid induced writhing method and radiant heat tail flicking method; anti-inflammatory activity was evaluated by HRBC membrane stabilization method and hypoglycemic activity by blood glucose level test. The carbon tetrachloride partitionate at 400 mg/kg induced significant decrease in the no. of writhes while the petroleum ether partitionate at 400 mg/kg showed promising activity compared to standard diclofenac sodium. Similarly, the petroleum ether partitionate elongates the reaction time significantly after administration of extract in radiant heat tail flicking method, suggesting central antinociceptive activity and at concentration of 2000 ?g/ml showed promising protection of HRBC in hypotonic solution compared with standard naproxen. On the other hand, in hypoglycemic activity, the ethyl acetate partitionate shows significant activity compared to standard metformin drug. Bangladesh Pharmaceutical Journal 19(1): 25-31, 2016